2020
DOI: 10.2147/dddt.s244059
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resveratrol Exerts Anti-Osteoarthritic Effect by Inhibiting TLR4/NF-κB Signaling Pathway via the TLR4/Akt/FoxO1 Axis in IL-1β-Stimulated SW1353 Cells</p>

Abstract: Osteoarthritis (OA) is associated with chronic low-grade inflammation. Resveratrol exerts protective effects on OA through its anti-inflammatory property; however, the mechanism of resveratrol on anti-inflammatory signaling pathways has not been fully elucidated yet. The aim of the present study was to investigate whether resveratrol-mediated PI3K/Akt expression is linked to TLR4/NF-κB pathway and the role of TLR4/Akt/FoxO1 axis in the anti-osteoarthritic effect of resveratrol. Methods: SW1353 cells stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…This nutraceutical has many health-benefiting properties, including its anti-inflammatory, antioxidant, and anticancer properties. By modulating major oxidative stress signaling pathways, resveratrol has become one of the most studied nutraceuticals in managing degenerative diseases such as OA [ 51 , 52 , 54 , 55 , 56 , 57 , 67 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…This nutraceutical has many health-benefiting properties, including its anti-inflammatory, antioxidant, and anticancer properties. By modulating major oxidative stress signaling pathways, resveratrol has become one of the most studied nutraceuticals in managing degenerative diseases such as OA [ 51 , 52 , 54 , 55 , 56 , 57 , 67 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…In vivo and in vitro studies provided more detailed mechanistic information on the resveratrol’s actions in modulating pain, reducing inflammation, and exerting a protective effect in OA patients [ 51 , 52 , 55 , 57 ]. Its protective effects were demonstrated in an in vivo model where resveratrol ameliorated inflammatory damage in a rat OA model [ 55 ] through its impact on the NF-κB and HO-1/Nrf-2 signaling pathway [ 52 ]. Resveratrol downregulated the expression of TNF-α, IL-1β, IL-6, and IL-18 and the caspase-3/9 activity.…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…And our study verified the therapeutic effect of RES on MCC cells by flow cytometry, which demonstrated that RES significantly reversed IL-1 β -induced apoptosis in the chondrocytes. Some studies verified that RES exerted protective effects on OA through its anti-inflammatory property by the NF- κ B pathway [ 25 , 26 ]. The present study agreed with previous studies, which revealed the anti-inflammation of RES on TMJOA by inhibiting the COX-2 gene expression, NF- κ B pathway, and downstream factors MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that NAM could effectively reduce the accumulation of IL-6 in the lung, and the cell experiments also showed that NAM could inhibit the expression of IL-6 by macrophages. IL-1β can activate Toll-like receptors in macrophages (Xu et al 2020 ), thus exacerbating the inflammatory response (Gabay et al 2010 ). Our research showed that NAM could reduce the expression of IL-1β in the lung, and we also found that NAM could inhibit the gene expression of IL-1β in macrophages.…”
Section: Discussionmentioning
confidence: 99%